Pay-for-Performance as a Strategic Tool Towards Effective Talent Management in Malaysia’s Financial Sector - Ng, Chia Nee (2016)
Talent scarcity in the Malaysian financial sector remains to be severe as talent mobility has surged significantly not only geographically, however also across sectors as the need for talent in financial services by other sectors is expected to rise. The war of talent will be further exacerbated in the coming years as talent poaching is rampant amongst local financial companies with the enactment of stringent financial acts and to a degree which could affect companies’ competitiveness. Therefore, the immediate response of employers as they experience rising intense talent supply will be to simply offer appealing remuneration. With this, reasonable reward is provided so that talented employees will not be preoccupied with the inequitableness of the situation and are able to concentrate on their jobs. As such, it is vital for companies to provide a good and competitive reward system to enable effective talent management.The main purpose of this research study is to examine the pay-for-performance (PFP) framework of the financial sector in Malaysia and its influence as a strategic tool in attracting, motivating, rewarding and retaining talented employees. Based on relevant literature review and theories, seven PFP schemes have been identified to evaluate its efficacy in talent management and overall, it is deduced that these seven PFP schemes are influential in managing talent. However, due to poor enactment of the reward process, talented employees have limited access to these PFP plans. Thus, HR managers need to undertake several tangible and intangible initiatives ranging from statutory inflation-based salary increment with relevant benchmarking, performance-based pay progression strategies, replacing seniority-based pay with PFP, employee involvement in reward system design, replacing performance evaluation with performance management system, appeal process, innovative HR technology, communication culture enhancement, flexible benefits, annual employee performance with flexible package of choice, instigation of peer-to-peer recognition, implementation of talent development, launching of ESOP in privately-held financial companies to the provision of above statutory contribution rate for employees provident fund, in order to address the problems or challenges faced.